Observation of intensity oscillations above X-ray bright points from the Hinode/XRT: Signature of magnetohydrodynamic oscillations in the solar corona - Kumar M.; Srivastava A.K.; Dwivedi B.N. (My University, 2025)
We analyse the temporal image data of the quiet Sun observed by the X-ray Telescope (XRT) onboard the Hinode spacecraft and Al-poly filter on 2007 March 31. We choose these temporal image data of ~30s cadence from 11:34:48 ut to 14:19:35 ut to study intensity oscillations above selected X-ray bright points (XBPs) with an exposure time 8.193s of each XRT image. Using the Fourier filtering method, we reconstruct X-ray light curves for the periods outside the cone-of-influence (COI) of their power spectrum. Using the standard wavelet software, we derive the power spectra of the reconstructed light curves which are generated by filtering the original X-ray time-series at the Fourier scale (54.55 min) outside the COI period (60.18 min) free from the edge effect and inappropriate long-term periodicities. This procedure provides statistically significant and globally distributed multiple periodicities in the intensity and global wavelet power spectra of the X-ray light curves derived from the selected coronal structures. We select seven XBPs to extract their respective X-ray light curves. We find the statistically significant observed periodicities (two or three) for XBP1, XBP2, XBP4, XBP5, XBP6 and XBP7, respectively, to be (28, 15) min, (50, 20) min, (60, 20, 12) min, (51, 23) min, (35, 23, 13) min, (49, 20) min and (35, 19) min. We interpret these observed periodicities in terms of the leakage of various harmonics of magnetoacoustic waves into the higher corona. Some BPs (XBP1, XBP3, XBP5 and XBP7) show the shift in the period ratio either as (P1/P2) < 2.0 or as (P1/P3)< 3.0. This period ratio shift provides the first most likely observational signature of the density stratification in these XBPs. Other BPs (XBP2, XBP4 and XBP6) show the shift in the period ratio (P1/P2) > 2.0, which may serve as evidence for magnetic field divergence with a significant effect on the various harmonics of magnetoacoustic waves. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.